A multi-year heavy metal analysis of 72 dark chocolate and cocoa products in the USA - Hands, Jacob M.; Anderson, Mark L.; Cooperman, Tod; Balsky, Jared E.; Frame, Leigh A. (Frontiers in Nutrition, 2024)
From 2014-2022, 72 consumer cocoa-containing products were purchased and analyzed for heavy metal contamination with lead (Pb), cadmium (Cd), and arsenic (As) in 4 distinct cohorts (2014, 2016, 2019, 2022). The thresholds used to assess heavy metal contamination were set to Prop 65 maximum allowable dose levels (MADLs) of 0.5 mcg/day, 4.1 mcg/day, 10 mcg/day for Pb, Cd, and As, respectively. Our analysis reports that 43%, 35%, and 0% of the products tested exceed Prop 65 MADLs for heavy metal concentrations, respectively, of Pb, Cd, and As, while 97.2% (70 of 72) fall below US FDA IRL limits established for Pb. Median concentrations of each metal tested were lower than even the conservative Prop 65 MADLs, indicating a potentially large effect of product outliers. This indicates that heavy metal contamination -in more than half of products tested -may not pose any appreciable risk for the average person when consumed as a single serving; however, consuming some of the products tested, or more than one serving per day in combination with non-cocoa derived sources heavy metals, may add up to exposure that would exceed the Prop 65 MADLs. Notably, "organic" products were significantly more likely to demonstrate higher levels of both Cd and Pb.